Hotel Pro Forma in a European context - Bener, Theresa (Peripeti, 2017)
In the following Bener discuss some examples of how the aesthetics of Kirsten Dehlholm and Hotel Pro Forma relate to tendencies in the European performing arts. All established stage auteurs of course have their unique artistic idiom, so although we can detect certain correspondences and similarities between Dehlholm and other artists, they will only concern specific aspects.